Integrated scheduling of hot rolling production planning and power demand response considering order constraints and TOU price. Issue 14 (29th March 2022) - Gong, Feixiang; Chen, Songsong; Tian, Shiming; Qin, Jian; Zhang, Haijing; Sun, Beibei; Yuan, Jindou; Jiang, Linru; Xu, Yuting; Wang, Yong
Abstract: When participating in demand response, the industrial adjustable load has the advantages of large capacity, high benefit, and easy management compared with commercial and residential loads. However, the stage of the production process is strongly coupled with the power consumption process, especially in the steel industry. Here, a multi‐objective optimization model for the optimal scheduling of hot rolling load considering the actual production operation conditions was proposed, the model was abstracted into a vehicle routing problem (VRP), which is a typical combinatorial optimization problem .To minimize the cost of electricity and the risk of delivery order default, this paper considered the jump penalty value between adjacent slabs simultaneously, constructed an integrated scheduling model of hot rolling shop scheduling and power demand response, and designed a multi‐objective production scheduling algorithm based on NSGA‐II to solve the problem. The results showed that the proposed method can realize the reasonable distribution of production load under the constraints of electricity price and production.